PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP EARNINGSS RESPONSE COEFFICIENT PADA PERUSAHAAN HIGH PROFILE - NAILA NUUR HIDAYATI; SRI MURNI (Jurnal Bisnis dan Akuntansi, 2009)
The aim of this study is to empirically prove the effect of the information of Corporate Social Responsibility (CSR) disclosed in the companies annual report on the value relevance of earnings (measured by Earnings Response Coefficient (ERC). Based on alternative infor-mation hypothesis, it is predicted that corporate social responsibility’s disclosure has negative effect on the ERC. The sample of this study are 37 companies which are selected by using purposive sampling method from 110 high profile’s company listed in IDX during 2006. To examine the hypothesis, it is used multiple regression analysis with interaction model, cross sectional ordinary least square method. The result indicate that information of CSR have a negative influence of earnings.